Effects of (+)-8',8',8'-trifluoroabscisic acid on alpha-amylase expression and sugar accumulation in rice cells - Kashem, M.A; Hori, H; Itoh, K; Hayakawa, T; Todoroki, Y; Hirai, N; Ohigashi, H; Mitsui, T (Planta, 1998)
The effects of (+)-8',8',8'-trifluoroabscisic acid (trifluoro-ABA) on alpha-amylase expression were studied in rice embryoless half-seeds, scutella, and suspension-cultured cells derived from the embryo, and the effects of the analog on sugar accumulation were also studied in scutella and suspension-cultured cells. Treatment with (+)-trifluoro-ABA strongly inhibited the gibberellic acid-inducible expression of alpha-amylase I-1 encoded by RAmy1A in the aleurone layers of embryoless half-seeds at the levels of transcription, protein synthesis, and enzyme activity. It was also found that (+)-trifluoro-ABA stimulated (i) the uptake of glucose from the incubation medium and (ii) the synthesis of sucrose in scutellar tissues and suspension-cultured cells of rice. The biological activity of (+)-trifluoro-ABA was found to be more potent and persistent than that of natural ABA. We further examined the effects of trifluoro-ABA on the expression of alpha-amylase I-1 in scutellar tissues and suspension-cultured cells. It was found that (+)-trifluoro-ABA did not inhibit the formation of alpha-amylase I-1 in the absence of external glucose. However, glucose and (+)-trifluoro-ABA cooperatively suppressed the formation of alpha-amylase I-1. Judging from these results, we conclude that the regulatory mechanism for the expression of alpha-amylase I-1 in the scutellar epithelium is distinguishable from that operating in the aleurone layer.